Incidence of cotton whitefly Bemisia tabaci (Gennadius, 1889) (Hemiptera: Aleyrodidae) infesting cucumber (Cucumis sativus L.) cultivars with reference to cultivar susceptibilities - El-Shazly Ezz El-Din Abd El-Samea (Polish Journal of Entomology, 2019)
Field experiments were carried out in Egypt to investigate the infestation rates of cotton whitefly Bemisia tabaci on five cultivars of cucumbers Cucumis sativus during two consecutive late summer seasons from 11 August to 28 October 2015 and 2016. The susceptibilities of the cultivars to infestation by this pest were examined. The five cultivars – Hayl, Nems, Beit Alpha Zena, Bahi and Wafier – were cultivated on a private farm in Mansheyet Saqqara village, Giza. The results showed that whitefly infestation peaks were high in September and October, but low in November in both seasons. The population densities of Bemisia tabaci eggs, nymphs and adults on all the cultivars were slightly higher in 2015 than in 2016. Numbers of B. tabaci eggs, nymphs and adults rose with increasing the temperatures in both seasons, and mean numbers of nymphs and adults also increased with decreasing RH% on all the cultivars. The combination of temperature and humidity was an important regulatory factor affecting B. tabaci development. The results of this study showed that high infestation peaks of B. tabaci occurred in September and October of both seasons. The present results were used to classify the degrees of susceptibility of these cucumber cultivars to B. tabaci infestation as susceptible (S), low resistant (LR) and moderately resistant (MR). It is important that these degrees of susceptibility be referred to the degree of resistance of each cultivar to insect infestation.